PEMANFAATAN ANALISIS SPASIAL SIG: PERENCANAAN LOKASI TPS 3R SEBAGAI STRATEGI PENGELOLAAN SAMPAH BERKELANJUTAN DI KABUPATEN GORONTALO - Paramata, Mulyani Zahra; Darwanto, Rindang Adhaini; Monoarfa, Zachra Putri Arfiani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
A sustainable alternative strategy to prevent the overcapacity of final disposal sites (TPA) is to strengthen waste management systems at the upstream level, particularly through the establishment and optimization of Reduce-Reuse-Recycle Waste Processing Facilities (TPS 3R). The selection of appropriate locations is a critical initial step to ensure the operational effectiveness and long-term sustainability of TPS 3R facilities. This study aims to identify potential sites that meet spatial and environmental criteria for the development of TPS 3R across five subdistricts in Gorontalo Regency. Spatial analysis was conducted using Geographic Information System (GIS) tools, applying buffer, scoring, and overlay techniques in ArcGIS. The analysis identified five optimal locations for TPS 3R development: Hutuo Subdistrict, Limboto (0°37'33.3